SWOT Analysis Determining Effective Business Strategy at Cafe XYZ - Agustin, Yulia; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Penalty This focused on formulating business strategies For A cafe, restaurant scrutinized to be taken SWOT analysis. Method qualitative digging deep researcher this, includes study literature For data collection. Assessment Results internal structure factor that Cafe XYZ has strength main in the form of Attractive interior design, strategic location, and quality material superior standard. However, weaknesses were also identified, namely capacity limited space, suboptimal management, and lack of amount power cut. From here factor external, research This find swell like dizziness trend Consumable coffee and sweets loyalty customers, but on the other hand there are also threat in the form of height amount walking and fluctuating price material standard. Undecided SWOT analysis, management cafe XYZ reviews the need formulation of effective strategies. This strategy covers effort dizziness promote, promote pedicure through digital platforms, and innovation product use maximize internal strength and leverage swell actual thing like that.